EKSPLORASI MAKNA RITUAL JARO ROJAB PADA MASYARAKAT CIKAKAK BANYUMAS : KAJIAN SEMANTIK - Risca Milanti, Christia; Widodo; Eka Yulia Astuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Jaro Rojab ritual is one of the traditions still preserved by the people of Cikakak. This ritual is not only a religious and customary activity held every 27th of Rajab, but it also carries various lexical and cultural meanings that reflect the identity, social, religious, and cultural values of the Cikakak community. This study aims to explore, understand, and describe the lexical and cultural meanings found in the Jaro Rojab ritual. This study employs a qualitative descriptive method with a semantic approach. The research subjects consisted of two informants the key figure and a traditional leader of Cikakak village who were selected using purposive sampling. Research data were collected through observation, interviews, and documentation, which were then analyzed using content analysis according to Moleong. Data validity was ensured through source triangulation and methodological triangulation.  The results of the study identified 22 lexical items related to the Jaro Rojab Ritual. These consisted of 7 lexical items regarding the ritual procession, 2 regarding the names of the venues where the ritual is held, 5 regarding ritual terms, 4 regarding ube rampe, 3 regarding ritual performers, and 1 regarding a figure within the ritual. From these lexical items, 22 lexical meanings and 21 cultural meanings were identified. Thus, the Jaro Rojab ritual not only serves as a tradition passed down from generation to generation but also acts as a medium for transmitting cultural values through language. A semantic analysis of the terms and utterances used in the ritual can serve as one effort to document and preserve the cultural knowledge of the Cikakak community amid the changing times.